2022
DOI: 10.1186/s13741-021-00237-w
|View full text |Cite
|
Sign up to set email alerts
|

Does application of honey improve surgical outcome in pilonidal cyst excision with secondary intention healing? A prospective randomized placebo-controlled clinical trial

Abstract: Background Pilonidal sinus disease (PSD) is a common chronic inflammatory debilitating illness caused by ingrowth of hair into the skin. Excision and healing by secondary intention is one of the acceptable managements. The post-operative wound care needs frequent and time-consuming follow-ups. Honey is considered to be a traditional remedy for wound healing. The current study aimed at finding if application of honey could improve surgical outcome in pilonidal cyst excision with secondary intent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In a clinical trial with 48 adult patients who underwent surgical resection for pilonidal sinus disease, patients receiving an unprocessed honey gel had significantly lower wound healing time and volume than a placebo gel. However, this study also found increased postoperative pain and analgesic consumption using the honey gel versus placebo, possibly due to honey's low pH causing a stinging or burning sensation 5,43 . Further studies are needed to determine the efficacy of honey, especially medical‐grade honey, for this specific disease.…”
Section: Rare Diagnoses and Special Casesmentioning
confidence: 78%
See 1 more Smart Citation
“…In a clinical trial with 48 adult patients who underwent surgical resection for pilonidal sinus disease, patients receiving an unprocessed honey gel had significantly lower wound healing time and volume than a placebo gel. However, this study also found increased postoperative pain and analgesic consumption using the honey gel versus placebo, possibly due to honey's low pH causing a stinging or burning sensation 5,43 . Further studies are needed to determine the efficacy of honey, especially medical‐grade honey, for this specific disease.…”
Section: Rare Diagnoses and Special Casesmentioning
confidence: 78%
“…However, this study also found increased postoperative pain and analgesic consumption using the honey gel versus placebo, possibly due to honey's low pH causing a stinging or burning sensation. 5,43 Further studies are needed to determine the efficacy of honey, especially medical-grade honey, for this specific disease.…”
Section: Rare Diagnoses and Special Casesmentioning
confidence: 99%